Promoting vocational students’ perception and achievement towards Chemistry: SPARE Learning Strategy for students majoring in Automotive Engineering - YusiArisandi, I WayanDasnaa, SumariSumari,HabiddinHabiddin, SuhadiIbnu, Subandi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Low Vocational High School students’ perception and achievement towards Chemistry has been a critical issue. Various studies have been carried out to find a proper solution for such issue. In Indonesia, Vocational High School aims to produce skillful graduates who are ready-to-work in the relevant area. In Vocational High School, Chemistry is a supportive course which is commonly lack of students’ interest. This study aimed to examine the improvement of vocational students’ perception and achievement of Chemistry after the implementation of vocational expertise-based teaching strategy named SPARE (Stimulation, information Processing, Application, Reflection, and Evaluation). This study involved 129 vocational high school students majoring in Automotive Engineering with 63 students as the experiment group and 66 students as the control group. Independent Samples Test, Mann-Whitney U Test, and N-Gain scores were employed to analyze the data. This study revealed that SPARE effectively improved students’ perception towards Chemistry and contributed significantly to increase their achievement. This study implies that implementing SPARE to other supportive courses at Vocational High School is a reasonable exercise.